The effect of Kinesio Taping on motor function in children with cerebral palsy: a systematic review and meta-analysis of randomized controlled trials - Lin, Xiaoguang; Zhang, Jiongliang; Wu, Minmin; Li, Jinting; Song, Wenjing; Zhu, Luwen (Frontiers in Neurology, 2025)
IntroductionKinesio taping (KT) is a well-known rehabilitation therapy technique used for treating children with cerebral palsy. However, no meta-analysis of kinesio taping has been conducted specifically for this purpose. This systematic review and meta-analysis aim to explore the effectiveness of kinesio taping in enhancing gross motor function, balance ability, and gait in children with cerebral palsy.MethodsA comprehensive database search was conducted using PubMed, Embase, the Cochrane Library, Web of Science, Cnki, Wan Fang, VIP, and the Physiotherapy Evidence Database (PEDro) to identify randomized controlled trials (RCTs) investigating the impact of kinesio taping (KT) on cerebral palsy. RCTs published until May 31, 2024, that met our predetermined inclusion and exclusion criteria were included. Data extraction, literature review, and assessment of the methodological quality of the trials were performed. The meta-analysis was conducted using StataSE version 16.ResultsThe primary outcome was Gross Motor Function Measure, Berg Balance Scale, Muscle Tension-Heel-Ear Test. The secondary outcomes were step frequency, step speed, step length. Our meta-analysis includes 378 children from 10 RCTs incorporated. Main result the Gross Motor Function Measure (GMFM D) (SMD = 1.00, 95%CI = 0.24–1.77, p = 0.01, I2 = 87.3), the Gross Motor Function Measure (GMFM E) (SMD = 0.84, 95%CI = 0.22–1.46, p = 0.008, I2 = 81.5%), the Berg Balance Scale (BBS) (SMD = 0.81, 95%CI = 0.20–1.42, p = 0.009, I2 = 76.3%). Muscle Tension-Heel-Ear Test (SMD = 1.57, 95%CI = 0.59–2.55, p = 0.002, I2 = 79.8%). The children showed significant improvements in gross motor function, balance and muscle tension compared to the results of the control group. The secondary step length (SMD = 0.46, 95% CI = 0.18–0.76, I2 = 47.3%, p = 0.002) had an improvement effect, but no significant effect on step frequency and step speed.ConclusionTo some extent, compared to the control group, the addition of kinesio taping improved motor dysfunction in children with cerebral palsy during rehabilitation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/search, identifier: CRD42024528254.